Insights into the impact of COVID-19 on household travel and activities in Australia – The early days of easing restrictions - Beck, Matthew J.; Hensher, David A. (Transport policy, 2020)
The COVID-19 disease continues to cause unparalleled disruption to life and the economy world over. This paper is the second in what will be an ongoing series of analyses of a longitudinal travel and activity survey. In this paper we examine data collected over a period of late May to early June in Australia, following four-to-six weeks of relatively flat new cases in COVID-19 after the initial nationwide outbreak, as many state jurisdictions have begun to slowly ease restrictions designed to limit the spread of the SARS-CoV-2 virus. We find that during this period, travel activity has started to slowly return, in particular by private car, and in particular for the purposes of shopping and social or recreational activities. Respondents indicate comfort with the idea of meeting friends or returning to shops, so authorities need to be aware of potential erosion of social distancing and appropriate COVID-safe behaviour in this regard. There is still a concern about using public transport, though it has diminished noticeably since the first wave of data collection. We see that working from home continues to be an important strategy in reducing travel and pressure on constrained transport networks, and a policy measure that if carried over to a post-pandemic world, will be an important step towards a more sustainable transport future. We find that work from home has been a generally positive experience with a significant number of respondents liking to work from home moving forward, with varying degrees of employer support, at a level above those seen before COVID-19. Thus, any investment to capitalise on current levels of work from home should be viewed as an investment in transport. •Aggregate travel has increased by 50% but is still less than two-thirds of that which occurred prior to COVID-19.•Motor vehicle travel rebounding more than other modes, those planning a return to train and bus intended to do so strongly.•Large increases in activity planned for shopping and social and recreation purposes.•People feel most comfortable with meeting with friends, going to the shops and visiting restaurants.•Working from home continues, and has been largely positive for those who have been able to do so..•Concern about the risk of COVID-19 has decreased significantly since the initial outbreak.